1974
DOI: 10.1139/x74-038
|View full text |Cite
|
Sign up to set email alerts
|

Bales Versus Polybags in Cold and Frozen Overwinter Storage of Nursery Stock

Abstract: Fall lifted white spruce, white pine, and red pine were stored overwinter 1969–70 at Orono Nursery, Ontario. Frozen (−4 °C) and cold (1.5 °C) storage conditions; bales and polyethylene bags were compared. The trees were planted in the spring at three locations, both 'early' (May 5–8) and 'late' (May 26–28). This report is based on survival, height, and terminal shoot measurements to the end of the second season.Storage of white spruce was successful, the polybag was the better container, and frozen storage the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1976
1976
1985
1985

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…85% (Mullin and Parker 1974) and 92% (Mullin and Bunting 1972). This may be partly due to the quality of the stock as the top-root ratio (Table 1) was well above the maximum of the working range given for 3-0 white spruce in Ontario nurseries; 2.5 to 4.5:l (Armson and Carman 1961), and was in the "top-heavy" class of Stoeckeler and Jones (1957).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…85% (Mullin and Parker 1974) and 92% (Mullin and Bunting 1972). This may be partly due to the quality of the stock as the top-root ratio (Table 1) was well above the maximum of the working range given for 3-0 white spruce in Ontario nurseries; 2.5 to 4.5:l (Armson and Carman 1961), and was in the "top-heavy" class of Stoeckeler and Jones (1957).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that white pine and red pine may be intermediate, and in that order (Mullin and Parker 1974;Mullin 1974a over a period of time such as "below 40°F for 20-30 days" (Nyland 1974b3, might be expressed in a simple formula. A negative degree-hardeningdays, D-H-D (from degree-days, Zasada 1973) with a basis of 50°F (Nyland 1974b), was prepared daily of the differences between 50°F and the daily minimum for soil temperature at 15 cm depth.…”
Section: Timing the Fall Lifting For Storage (Degree-hardening-days)mentioning
confidence: 99%
“…In Ontario frozen storage (-3OC) has generally been conThe success of overwinter storage of white pine (Pinus strobus L.) varies with lifting date and storage temperature (Mullin and Parker 1974). Lifting as late as possible in the fall has been considered one way to improve success (Williams and Rambo 1967, Mullin and Parker 1974, Nyland 1974a).…”
Section: Introductionmentioning
confidence: 99%
“…Lifting as late as possible in the fall has been considered one way to improve success (Williams and Rambo 1967, Mullin and Parker 1974, Nyland 1974a). However, earlier lifting is sometimes necessary to avoid freeze-up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation